The pressure of Europeanisation : from post-communist state administrations to normal players in the EU system - Lippert, Barbara, 1962- 1962- (Europäische Schriften, 2005)
This book deals with EU-driven "Europeanisation" of the public administrations in live countries of Central and Eastern Europe that joined the EU in 2004. Since the early nineties preparation for membership has gradually worked as a factor and incentive to shape and develop structures and institutions capable of meeting the obligations and needs of a future EU member state. While challenges arise from both legacies of the past and new demands after effective membership the authors argue that the five new members will most likely develop into normal players in the EU system.